A Survey of Parents’ Perspective of Receiving a Developmental Diagnosis for Their Child - Stacey D. Miller; Maria Juricic; Jaimy Coates; Jeffrey N. Bone; Ash Sandhu; Kishore Mulpuri; Maureen O’Donnell (Children)
Receiving a diagnosis, such as cerebral palsy (CP), can have lasting impacts on caregivers and families. Previous literature has described that caregivers wish to receive a diagnosis together, without delay, in a private, direct, honest, and sympathetic way. This study aimed to understand the experience of caregivers of children with cerebral palsy (CP) or similar conditions when receiving a diagnosis for their child.: Caregivers of children and youth aged 0–18 years with CP or a similar physical condition completed a survey investigating who first provided a diagnosis, and the way it was provided. Questions were based on the pediatric SPIKES framework. Caregivers were asked how receiving a diagnosis could have been improved. Thematic analysis of qualitative data were performed.: A total of 180 surveys were completed. Mean age at diagnosis was 19.0 (SD 25.7) months. Most caregivers reported the healthcare provider was sympathetic and understanding (75%) and clear and direct (69%). Only 25% of caregivers recalled being directed to where to find information; only 37% reported being told what their child does well or is expected to do well. Thematic analysis revealed three themes: (1) less waiting, (2) more compassionate communication, and, (3) information and support to move forward: Caregivers wanted the diagnosis to be timely and provided with compassion. Requests for greater information on the diagnosis, available support, and their child’s future, suggest that greater care to support families in the aftermath of receiving a diagnosis is also needed.